2020
DOI: 10.1002/ajmg.a.61493
|View full text |Cite
|
Sign up to set email alerts
|

The characterization of hypodontia, hypohidrosis, and hypotrichosis associated with X‐linked hypohidrotic ectodermal dysplasia: A systematic review

Abstract: The objective of this study was to review the published literature on X‐linked hypohidrotic ectodermal dysplasia (XLHED) for the prevalence and characteristics of three features of XLHED: hypodontia, hypohidrosis, and hypotrichosis. A systematic search of English‐language articles was conducted in May 2019 to identify publications with information on any of the three features of XLHED. We excluded studies with five or fewer participants, that did not specify X‐linked inheritance or an EDA mutation, and discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 33 publications
0
17
0
2
Order By: Relevance
“…Este fenómeno fue descrito incluso antes de la identificación de EDA, con una tasa de mutación en la espermatogénesis de 3.5:1 con respecto a la ovogénesis 27 . En los estudios realizados en mujeres de familias con DEHLX se describe una frecuencia alta de mujeres heterocigotas, quienes en su mayoría presentan la sintomatología 4,5,25,[28][29][30] .…”
Section: Discussionunclassified
“…Este fenómeno fue descrito incluso antes de la identificación de EDA, con una tasa de mutación en la espermatogénesis de 3.5:1 con respecto a la ovogénesis 27 . En los estudios realizados en mujeres de familias con DEHLX se describe una frecuencia alta de mujeres heterocigotas, quienes en su mayoría presentan la sintomatología 4,5,25,[28][29][30] .…”
Section: Discussionunclassified
“…The number of teeth can range from more than a dozen, through several, or the lack of all permanent teeth and even, in some cases the lack of both dentitions is present [4,31,35,36] . Studies have found that the most frequent missing teeth are the upper lateral incisors, upper and lower premolars [37] . The oral manifestations can occur in the shape of the teeth, size, the number of teeth present and can even affect the normal development of the alveolar ridge, making it a challenge when planning treatment, because the bone can compromise the results.…”
Section: Oral Manifestationsmentioning
confidence: 99%
“…of rare congenital conditions affecting the normal development and/or homeostasis of two or more ectodermal derivatives including skin, teeth, hair, nails, and eccrine glands. [1][2][3] Hypohidrotic ED is estimated to affect at least 1/5000 to 10 000 newborns. 1 X-linked hypohidrotic ED (XLHED; OMIM 305100), 3 is the most common subtype of EDs, with an incidence of 1/50 000 to 100 000 males.…”
mentioning
confidence: 99%
“…1 X-linked hypohidrotic ED (XLHED; OMIM 305100), 3 is the most common subtype of EDs, with an incidence of 1/50 000 to 100 000 males. [1][2][3] XLHED is characterized by a clinical triad of hypotrichosis, hypo-, oligo-or anodontia, and hypo-or anhidrosis. 2,3 XLHED is associated with the EDA gene located at (Xq12-q13.1), leading to loss or dysfunction of the signaling protein EDA, 3 a critical signaling unit involved in the interaction between the ectoderm and the mesoderm.…”
mentioning
confidence: 99%
See 1 more Smart Citation